The influence of tides on the North West European shelf winter residual circulation - Tinker, Jonathan; Polton, Jeff A.; Robins, Peter E.; Lewis, Matthew J.; O’Neill, Clare K. (Frontiers in Marine Science, 2022)
Tides contribute to the large-scale residual circulation and mixing of shelf seas. However, tides are typically excluded from global circulation models (GCMs) so their modelled residual circulation (and mixing) in shelf seas may be systematically wrong. We focus on circulation as it is relatively unexplored, and affects shelf temperature and salinity, potentially biasing climate impact studies. Using a validated model of the North West European Shelf Seas (NWS), we show the essential role of tides in driving the residual circulation, and how this affects the NWS temperature and salinity distribution. Over most of the NWS, removing the tides increases the magnitude of residual circulation while in some regions (such as the Irish Sea) it leads to a reduction. Furthermore, we show that modelling the NWS without tides leads to a cold fresh bias in the Celtic Sea and English Channel (of >0.5°C, and >0.5 psu). This shows that NWS tidal dynamics are essential in the transport of heat and matter, and so must be included in GCMs. We explore two processes by which the tides impact the residual circulation and investigate whether these could be parameterised within non-tidal GCMs: (1) Enhancing the seabed friction to mimic the equivalent energy loss from an oscillating tidal flow; (2) Tidal Phase-driven Transport (TPT), whereby tidal asymmetry drives a net transport due to the phase between tidal-elevation and velocities (equivalent to the bolus term in oceanographic literature). To parameterise TPT, we calculate a climatology of this transport from a harmonic analysis from the tidal model and add it as an additional force in the Navier Stokes equations in the non-tidal model. We also modify the bed drag coefficient to balance the bed stress between the simulations – hypothesising that using this modified drag coefficient will simulate the effect of the tides. This tends to improve the mean and variability of the residual circulation, while the TPT improves the spatial distribution and temporal variability of the temperature and salinity. We show that our proof-of-concept parameterisation can replicate the tidally-driven impact on the residual circulation without direct simulation, thus reducing computational effort.